2013
DOI: 10.1007/s00213-013-3028-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic social defeat stress on behavior and choline acetyltransferase, 78-kDa glucose-regulated protein, and CCAAT/enhancer-binding protein (C/EBP) homologous protein in adult mice

Abstract: The present study demonstrated that chronic social defeat stress in mice produces stress-related behaviors. Different response patterns were noted for Grp78 and chop expression among the groups in terms of brain regions and time-course effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…When testing the mice on D30, no deficit in the short-term memory of CSDS-subjected animals was observed in ITI1 conditions, but the memory performances of stressed-HEC mice were significantly altered in the ITI24 ones. These data corroborated previous studies that also described impaired cognition in social-defeated mice using the NOR test1641 with mnesic alterations in that case recorded at both short and long term, but measured 5 days only after the last defeat session. Interestingly, we showed that long term memory was still affected 3 weeks after CSDS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When testing the mice on D30, no deficit in the short-term memory of CSDS-subjected animals was observed in ITI1 conditions, but the memory performances of stressed-HEC mice were significantly altered in the ITI24 ones. These data corroborated previous studies that also described impaired cognition in social-defeated mice using the NOR test1641 with mnesic alterations in that case recorded at both short and long term, but measured 5 days only after the last defeat session. Interestingly, we showed that long term memory was still affected 3 weeks after CSDS.…”
Section: Discussionsupporting
confidence: 91%
“…Following repeated exposures to aggressive resident CD-1 mice, intruder C57BL/6J mice display various behavioral deficits such as social avoidance, anxiety-like phenotype, despair-like behavior and a reduction in sweet preference111213. In addition, CSDS-exposed animals also exhibit cognitive impairments141516, related to those observed in patients subjected to social stress, that suggest a marked dysregulation of the hippocampus, a brain structure known to play a crucial role in memory processes17, and to be directly altered by social stress18.…”
mentioning
confidence: 99%
“…Precedent preclinical and clinical studies revealed the involvement of ER stress in the pathophysiology of depression and stress-induced neurological complications [12,13,48,49]. Elevated ROS and cytokines can trigger the ER stress response which ultimately leads to cell damage [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…However, under prolonged ER stress condition, cells may undergo apoptotic pathway through upregulation of C/EBP homologous protein (CHOP) which eventually leads to apoptosis cell death [11]. Recent studies indicated the key role of ER stress in the pathophysiology of depression and cognitive impairment [12,13]. ER stress is associated with different inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of social defeat stress was performed as previously reported (Golden et al, 2011; Zhao et al, 2013; Yang et al, 2015a, 2016b; Zhang et al, 2015b). Every day the C57BL/6 mice were exposed to a different CD1 aggressor mouse for 10 minutes total for 10 days.…”
Section: Methodsmentioning
confidence: 99%